The interplay of Ownership, Governance, and Capital structures with Firm Performance: Insights from the Manufacturing sector in Pakistan - Rasheed, Muhammad Haroon; Muhammad Shahid Rasheed; Rabia Farooq (UW Journal of Management Sciences, 2024)
Purpose: This study investigates the effect of ownership control size and corporate governance mechanisms on the performance of the Pakistani manufacturing sector Design and Methodology: The study uses input and output characteristics as predictors to evaluate efficiency performance through the use of data envelopment analysis (DEA). It uses Ordinary Least Squares regressions to look at the association between ownership control size, corporate governance characteristics, and efficiency performance using a panel dataset that spans from 2001 to 2022. Findings: The results imply that the differences in cash flow, seat control, and voting rights have no effect on how efficiently businesses operate in Pakistan. However, there is a strong positive correlation between performance efficiency and organisational size and corporate governance characteristics. Implications: The results suggest that investors, especially those who are minority stakeholders, should proceed with prudence when making investments in companies whose control and ownership are not aligned. In theory, this research adds to the body of knowledge by validating results from past studies on the success of businesses in a neglected area like Pakistan. We also take into account effect variables that go beyond the data that is currently available. All things considered, this study contributes to increased trust about the importance of ownership structure, size, and corporate governance factors in companies that are subject to market supervision.